Developing an internationalization strategy for Altis hotels: The analysis of an opportunity in Angola - Mota, Catarina Gonçalves Garcia Gomes (2014)
The tourism industry, under a leisure, business or other purpose, has been subject to an intensive change not only regarding the appearance of a new type of offer (more informal) and the internet as a tool to enable a cost efficient marketing and awareness of small businesses, but also on the demand side which increased mostly due to globalization. Thus, new drivers to compete and especially to grow in this market became more relevant, such as differentiation strategies and cost-efficient initiatives. This applied project is focused on an internationalization strategy in the hospitality sector of a family-owned Portuguese company, Altis Hotels, which doesn‟t have operations across borders, to a new market, Angola. The internationalization process is positioned as an instrument to expand the company‟s sales and this first international step can be used as a learning platform for a wider internationalization strategy of the Group in the future. The applied project aims to analyze the Group‟s current operations, especially Altis Prime, the concept (aparthotel, targeting long-stays) intended to implement in Luanda, Angola‟s capital. Also, it intends to highlight Angola‟s current environment and in particularly the hospitality sector, which is in a growth stage. Finally, the tangible and intangible resources required for the internationalization process are identified as well as the recommended strategy to pursue. The purpose of this applied project is to be an anlytical tool mostly for Altis Hotels and also for other players in this industry, in order to understand the strategic importance, benefits, obstacles and risks of an internationalization process.